2004
DOI: 10.1089/154732804323099226
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Stem Cells Using Trehalose: Evaluation of the Method Using a Human Hematopoietic Cell Line

Abstract: While stem cell cryopreservation methods have been optimized using dimethylsulfoxide (DMSO), the established techniques are not optimal when applied to unfertilized human embryonic cells. In addition, important questions remain regarding the toxicity and characteristics of DMSO for treatment of stem cells for clinical use. The objective of this study was to establish an optimal method for cryopreservation of stem cells using low concentrations (0.2 M) of trehalose, a nontoxic disaccharide of glucose, which pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(105 citation statements)
references
References 56 publications
4
98
0
3
Order By: Relevance
“…Although DMSO is regarded as relatively nontoxic, the clinical use of frozen/thawed cells treated with DMSO can cause many adverse effects and toxic reactions [7][8][9][10][11][12][13][14]. It has also been reported that DMSO is not only cytotoxic but it also induces differentiation of stem cells to cardiac or neuronal like cells when added to the cell culture medium [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DMSO is regarded as relatively nontoxic, the clinical use of frozen/thawed cells treated with DMSO can cause many adverse effects and toxic reactions [7][8][9][10][11][12][13][14]. It has also been reported that DMSO is not only cytotoxic but it also induces differentiation of stem cells to cardiac or neuronal like cells when added to the cell culture medium [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, imperative to reduce the toxicity by the removal of DMSO prior to clinical use. However, the total removal of DMSO from the frozen/thawed cells is costly and time consuming and invariably results in cell loss and clumping [7,8]. Therefore, it is necessary to develop cryopreservation protocols either with lower concentrations of DMSO or with nontoxic alternatives to DMSO.…”
Section: Introductionmentioning
confidence: 99%
“…These cells also retained the potential to multilineage engraftment in nonobese diabetic-SCID mice [22]. Extracellular and intracellular loaded trehalose also proved to be an effective CPA for HSCs as suggested by one of the lab report [23]. Trehalose, and to some extent sucrose can stabilize proteins as well as lipid bilayer.…”
Section: Introductionmentioning
confidence: 88%
“…Trehalose forms a glass, a crucial process in cell preservation and storage in a dry state even at high temperatures and moisture content. The major problem in using this disaccharide is the impermeability of the plasma membrane leading to considerable difficulty in introducing high concentrations of the polymer in the cell cytoplasm (Buchanan et al 2004). Major manipulations, like cell permeabilization, need to take place first, but this may affect signalling pathways due to cell receptor and membrane channel damages.…”
Section: General Aspects Of Stem Cell Cryoconservation Conditions Cementioning
confidence: 99%